THE QUALITY OF SURVEY SCALES FOR MEASURING INFORMATION PRIVACY CONCERNS ON SOCIAL NETWORK SITES: A SYSTEMATIC REVIEW - Bartol, Jošt; Petrovčič, Andraž; Vehovar, Vasja (AoIR Selected Papers of Internet Research, 2021)
Information privacy concerns (IPCs) play an important role in user behavior on social network sites (SNSs). They are associated with self-disclosure behavior, enjoyment, and, perhaps most importantly, a user’s intention and ability to form and sustain social ties on SNSs. While conceptual integration of different approaches to studying IPCs has already been pursued, prior research has pointed to potential problems with respect to the survey measurements of IPCs. More specifically, a plethora of self-assessment scales have been developed but the differences among them have not yet been systematically elaborated, and this is further complicated by many methodologically questionable adaptations of existing IPC survey scales to ever-emerging online contexts and SNS platforms. Accordingly, this study comprises a systematic literature review based on the COSMIN methodology to comprehensively examine the quality of survey scales used for measuring IPCs among SNS users. The results have unveiled significant variety with 35 uni- or multidimensional survey scales used in 71 articles published since 2009. Many of the scales are of questionable quality in terms of structural validity, and only a few of the studies tested them for measurement invariance. Nevertheless, we identified some scales that are promising candidates for future use, although further testing and potential improvements are needed. Our findings could also act as the foundation for a unified measurement approach to IPCs that could be used across different SNSs platforms.